Institutions, competitiveness and cognitive ability - Syngjoo Choi; Byung-Yeon Kim; Jungmin Lee; Sokbae Lee (Centre for Microdata Methods and Practice (cemmap), 2020)
We investigate whether growing up in a socialist country affects the development of competitiveness by comparing three Korean groups in South Korea, born and raised in three countries with distinct institutional environments: South Korea, North Korea, and China. We examine the effect of home country experiences on competitiveness using laboratory experiments. Results show that North Korean refugees are significantly less competitive than South Koreans or Korean-Chinese immigrants. Ultimately, we find that the lower cognitive ability of North Koreans is a crucial determinant for the deficiency of competitiveness, while we fail to find evidence for direct effects of socialist institutions. Analysis through the lens of a choice model with probability weighting uncovers the effects of cognitive ability not only on expected performance but also on subject belief about winning and aversion for competition.
Keywords: C92; P20; 330; Piece Rate; Tournament; North Korea; Institution; Laboratory Experiment